Autism: early childhood education as an intervention scenario - Nunes, Débora; Araújo, Eliana Rodrigues (Education Policy Analysis Archives, 2014)
In recent decades, the effectiveness of early intervention programs for children with autism has been widely investigated. The importance of early and intensive care for this population is grounded in principles of neuroplasticity and developmental theories. The scientific literature documents the need for including children younger than five in early intervention programs, for a minimum of 25 hours per week. In this case, early childhood education settings and preschools become highly-promising educational scenarios for implementing intervention. In addition to working with children (birth-5) in full or part-time schedules, these educational programs focus on the integral development of the child, including physical, psychological, intellectual, and social aspects. The purpose of the current article is to describe the principles of early intervention, with an emphasis on best practices directed toward people with autism. Additionally, the relevance of this type of intervention in the context of early childhood education settings in Brazil is further discussed.